Ecthyma gangrenosum in a previously healthy patient - Ilkay Bozkurt; Esra Pancar Yuksel; Mustafa Sunbul (Wolters Kluwer Medknow Publications, 2015)
Ecthyma gangrenosum is a rare skin infection caused by Pseudomonas aeruginosa. It is usually seen in immunocompromised and critically ill patients. We report one such case in a previously healthy 20-year old male. Ecthyma gangrenosum can occur in healthy patients without bacteremia.